INTERAÇÃO DE FALA EM SITUAÇÃO DE CONFLITO: PAPÉIS INTERACIONAIS DO(A) MEDIADOR(A) EM UMA AUDIÊNCIA DE CONCILIAÇÃO NO PROCON - Silveira, Sonia Bittencourt; Gago, Paulo Cortes (Intercâmbio, 2010)
This paper focuses on three interactional roles enacted by the mediator in a Confrontation Session at Procon: 1) the orchestrator; 2) the expert; and 3) the negotiator. Analysis is based on a case study, following the Interactional Socilinguistics and Conversation Analysis approaches to discourse.